Gestión y Desarrollo Turístico de la Playa Punta Estrada, Cantón Santa Cruz, Provincia de Galápagos - Santillán Salazar, Doménica Valentina (2019)
The present research project called “TOURIST MANAGEMENT AND DEVELOPMENT OF THE PUNTA ESTRADA BEACH, CANTON SANTA CRUZ, and PROVINCE OF GALÁPAGOS” was carried out in conjunction with the Municipal Autonomous Decentralized Government of Santa Cruz about the problems that were detected with analysis of the variables. Galapagos is the star product, natural resources have made this destination is listed as one of the seven wonders of the world, the Santa Cruz Canton has several beaches that preserve its scenic beauty, one of them Punta Estrada Beach. The management allows the tourism development to have an effect of planning, organization and direction within the area to be studied, developing in a primordial way since the primary source of economic income for the Punta Estrada neighborhood is tourism. However, the activities that take place every day need a better organization, helping to improve the quality of tourism management and allowing tourism development to generate more significant benefits for the community. The hypothesis test are carried out through the statistical program SPSS version 23, which allows relating the management, the tourism development, as well as the dimensions: Planning, Organization, Organization, an Management with the tourist development for Punta Estrada beach. Taking into account that the research is essential because it provides solutions to the problems that have been detected in it since there is a significant relationship between the variables studied The proposal of Management Plan for the beach Punta Estrada will give information on the competitive advantages of the attraction, implementing strategies that help mitigate the problems that have been detected. I am contributing to tourism management and development for both tourism managers from the Santa Cruz canton, as well as for accommodation establishments in the Punta Estrada neighborhood